A new species of the genus Arrenurus Duges, 1834 (Acari: Hydrachnidia: Arrenuridae) for the Turkish fauna: Arrenurus (Truncaturus) corsicus (E. Angelier, 1951) - Esen, Yunus; Erman, Orhan (Tubitak Scientific & Technological Research Council Turkey, 2013)
Arrenurus (Truncaturus). corsicus (E. Angelier, 1951) is newly recorded for the Turkish fauna. It can be easily distinguished from other Truncaturus species by the pedipalpal femur with numerous hair-like setae medially, elongated idiosoma, and anterior coxae extending beyond anterior idiosoma margin.
Keywords: Acari; Arrenurus; Truncaturus; new record; Turkey